Tourism, Ecology, and Sustainability: The Poetics of Self-Making - Sairsingh, A Marie (International Journal of Bahamian Studies, 2019)
This paper explores, within an ecocritical frame, the work of two Bahamian poets that focus attention on such issues as pollution, neglect, commodification of natural resources, and the eco-social concerns of sustainability. The piece engages a brief discussion of the ways in which their poems critique power relations within national, multinational, and global spaces. The essay examines their poetic discourse on transnational corporations which operate on principles similar to those of the plantation economies that preceded them, ultimately continuing the practice of exploitation of Caribbean labour for wealth accumulation and bodily pleasures. Strachan and Limerick’s poetry functions to reclaim a sense of self, a sense of place as well as to recover a sense of history and forge a more sustainable relationship to the land and to environmental stewardship.